The Fall and Rise of The Contingency Theory of Leadership - Ary Suharyanto; Rizky Dwi Lestari (Iapa Proceedings Conference, 2020)
This article aims to look at the development of The Contingency Theory of Leadership which had developed in the 1970s, but declined in the 1990s, and has begun to be considered relevant again in handling major crises in recent years, including Covid-19. The study used a descriptive qualitative method to review the related literature. The Contingency Theory of Leadership with the main approach to leadership appropriate depending on the environmental situation that arises in the context of a particular action or behavior. Discovered in 1964 by Fiedler, then expanded in 1970, slowly declining until the 2010s. The number of catastrophes and major disasters in the world proves that the response of a leader to a crisis that is considered successful is one that can adapt to the context and circumstances. Some of the leader’s characters that are relevant in crises are Achieving Situational Awareness, Adaptive Decision Making, Communication, Energy Management, and Learning. A crisis is a situation that requires high leadership sensitivity. It takes a certain character that can help with proper handling both before, during and after a crisis.